ANEMIA IN DIABETIC PATIENTS WITHOUT MICROALBUMINURIA; IN RELATION TO TYPE OF DIABETES, GLYCEMIC CONTROL AND hs-C REACTIVE PROTEIN LEVELS - Hussein, Ali Mohammed Ali; Ali, Shatha H; Rahma, Abbas M; Al-Shami, Adeeb Abbas (Al-Nahrain Journal of Science, 2018)
Recent studies have highlighted on association between anemia and the development and progression of diabetic nephropathy. There is also an increased cardiovascular risk in patients with diabetic nephropathy and a clear association between anemia and abnormal cardiac function, although most patients in the previous studies have type 2 diabetes mellitus. The present study focused on the possible variations in hematological parameters as well as hs-CRP levels in anemic type 1 and type 2 diabetics without microalbuminuria, in relation to their glycemic indices. The study groups compromised of 50 diabetic patients (25 with type 1 and 25 with type 2) who had been selected to have haemoglobin levels below the gender specific normal range with negative microalbuminurea, in comparism to two control groups of 16 and 18 healthy subjects, respectively,whom are age and sex matching of type 1 and type 2 patients.For this the patients blood specimens were taken for testing blood levels of haemoglobin, red blood cells count,reticulocyte count, Hb A1C levels; as well as fasting serum glucose, serum insulin, C-reactive protein levels. The results indicated that anemia in both types of diabetes was not related to any of the RBC- indices (MCV, MCH, MCHC), results are not shown, but it’s related to lowered total number of RBC as compared to their controls. Meanwhile,their was no evidence of an increased reticulocyte in the studied groups of either types of diabetes, indicating a defective erythropoiesis rate, although the selected patients were without detectable nephropathy (−ve testing for microalbuminuria). Furthermore, the reduction in RBC count was not significantly correlated with glycemic indices (FPG, FPI, HbA1C, QUICKI). However, hs-CRP levels were significantly elevated in diabetic patients, but CRP levels were significantly correlated with fasting serum insulin in type 2 diabetics,but not in type1. Which may indicate a role for inflammation in type 2 diabetes in contribution to insulin resistance that may provide an additional risk factor for cardiovascular diseases in this type of diabetic whom have anemia as well.